Effect of Garden Cress (Lepidium Sativum) Extracts on Aflatoxin B1 in Rats - Abou Taleb, S. T - A, M. Yossef - M, I. Sanad - M. Sh. Abbas (Arab Journal for Sciences and Research Publishing, 2015)
Crude dichloromethane and methanolic extracts of Lepidium Sativum seeds Belong to family Brassicaceae, were used in this work to study their efficiency to relief Aflatoxin B1 in rats. The more effective of dichloromethane extract which decreased AflatoxinB1 rate from 7.5 to 1.0ppb at a dose of 300mg/kg body weight comparing with Silymarin which reduced AflatoxinB1 to 0.97ppb in concentration of 100mg/kg after 5weeks, followed by methanolic extract which showed the mean value of 1.2ppb. Also, the more effective treatment were Silymarin in concentration of 100mg/kg and dichloromethane extract, followed by methanolic extracts of Lepidium Sativum seeds for blood tests in Aflatoxin B1 in rats, e.g. serum marker enzyme parameters (SGOT, SGPT, ALP and Bilirubin), kidney functions (Creatinine and Urea), liver functions (ALT, AST, Total proteins, Albumin and Globulins), lipid profile (triglycerides, total cholesterol, HDL, LDL and vLDL) haematological parameters (HB, RBCs, Plt and WBCs),comparing with control rats.